Rethinking the reflective praxis of the name Social Science: Pedagogical ‘mischief’ in the Grade 4 to 9 Social Science curriculum (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
The article depicts the global history of the Social Science (SS) curriculum to illustrate that already by the 19th century Geography and History had been divided. The influence of non-integration of the SS was mainly by Geographical determinism which promulgated that the natural environment prescribes how people live, suggesting that all people living in a specific natural environment would respond in the same way when engaging with their environment. Such thinking inferred that human agency and culture had no role in such interaction. As a result some historians have neglected the environment in the study of History, which in turn served to further set boundaries for integration in SS. South Africa also subscribed to such a division as policy makers stipulated categorically in the Curriculum Assessment Policy Statement (CAPS) of Grade 4 to 9 that, SS is integrative in nature but has to be taught and administered as distinct Geography and History components. Integration occurs administratively when exam marks have to be combined as one to comprise SS – which is mischievous as it does not depict the reflective praxis of the subject pedagogically. The teaching and learning in terms of the content is divided into Geography and History but the summative is the only indicator of an integrated subject. From literature surveyed no investigation on the set topic has been undertaken in SA. The article thus proposes that non-integration of SS pedagogically speaking is ‘mischievous’ in the teaching and learning of SS in schools because the name negates what occurs practically in the teaching of the subject. The article through qualitative research drawing from interviews of trainee teachers enrolled in the Post Graduate Certificate Education doing SS at the University of KwaZulu- Natal enlightens the ‘mischiefs’ embedded in the SS curriculum. Drawing from some of the trainee teachers’ views the conclusions and recommendations of the article are that, SS has to be integrated because as is it is pedagogically misleading and compromises the quality of teaching in the learning area. This implies that, SS is an integrated subject and has to be taught as such because Geography cannot be taught without History or vice versa, because the one without the other equates with an incomplete learning area.
Keywords: Integration; Pedagogy; Geography; History; Social Studies; Mischief